DINAMIKA JALUR SUTRA - Abimanyu Rizky Ilahi; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This Journal will discuss about the History of the Silk Road which was mapped and used by silk traders going west to other realms beyond China’s influence. the silk road existed for a thousand years until the collapse of the last Chinese Dynasty under the nationalist. Trough progress made under Deng’s, Jiang’s, Hu’s, and Xi’s Communist Regime, the Silk Road is able to operate again under a new framework, the Belt and Road Initiative (BRI). Keywords: Austerity Measures, BRI, Debt Trap, Greek Economic Crisis